Ethical, legal and social implications of rare diseases and orphan drugs in Europe: meeting report of a Brocher symposium. (October 2013) - Picavet, Eline; Cassiman, David; Pinxten, Wim; Simoens, Steven
Ethical, legal and social implications of rare diseases and orphan drugs in Europe (Brocher symposium) Geneva, Switzerland 18–19 April 2013 As part of the Scientific Program of the Fondation Brocher, a two-day symposium on orphan drugs and rare diseases was held on the shores of Lac Léman in Geneva. Specific focus was on the ethical, legal and social implications of rare diseases and orphan drugs in Europe. The symposium gathered about 30 international stakeholders and experts, representing different scientific disciplines, the pharmaceutical industry and patient representatives.